Carbonylative Suzuki–Miyaura Coupling Reactions of Aryl Iodides with Readily Available Polymer-Immobilized Palladium Nanoparticles - Yasukawa, Tomohiro; Zhu, Zhiyuan; Yamashita, Yasuhiro; Kobayashi, Shu (Synlett, 2021)
Polysilane/alumina-supported palladium nanoparticle catalyzed carbonylative Suzuki–Miyaura coupling reactions under ligand-free conditions have been developed to synthesize diaryl ketones. High yields and selectivities were achieved even with low catalyst loading under atmospheric pressure of CO gas. A variety of aryl iodides and arylboronic acids could be utilized to afford the diaryl ketones in excellent yields. Moreover, the ligand-free immobilized palladium nanoparticles could be recovered by simple filtration and the catalytic activity could be maintained for several runs.
Keywords: carbonylative Suzuki–Miyaura coupling; heterogeneous catalyst; palladium catalyst; nanoparticle; diaryl ketones